The Correlation Between Students’ Writing Anxiety and B2 Level Achievement in Writing Proficiency - Adianti, Astrid Dwi; Fakhruddin, Zulfah; Tjalla , Magdahalena; Kalsum, Kalsum (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
Achieving B2-level writing proficiency based on the Common European Framework of Reference for Languages (CEFR) remains a challenge for many EFL university students. Beyond linguistic limitations, writing anxiety encompassing somatic, cognitive, and avoidance dimensions constitutes a critical affective barrier influencing students' writing performance. This study examined the correlation between students' writing anxiety and their B2-level writing proficiency in an EFL context at a State Islamic Institute in Indonesia. A quantitative correlational design was employed, involving 42 fourth-semester students of the English Education Program. Writing anxiety was measured using the Second Language Writing Anxiety Inventory (SLWAI), while writing proficiency was assessed through an IELTS Writing Task 2 test aligned with CEFR B2 descriptors. Data was analyzed using descriptive statistics and Pearson Product-Moment Correlation. The findings revealed that 85.7% of students experienced moderate anxiety, while 14.3% experienced high anxiety, with no students in the low-anxiety category. Regarding proficiency, 54.8% were at the B1 level and 45.2% reached B2. A statistically significant moderate negative correlation was found (r = −0.452, p = 0.003 < 0.05), confirming that higher writing anxiety is associated with lower B2 writing performance. The study interprets these findings through the lens of Krashen’s (1982) Affective Filter Hypothesis, Bandura’s (1997) Self-Efficacy Theory, and Sweller’s (1988) Cognitive Load Theory. Pedagogical implications encompass the adoption of low-anxiety classroom environments, process-based writing instruction, and structured feedback strategies to support CEFR-aligned writing development.